Digital Disruption: Landscape of E-Business for Competitive Advantage - Baskoro, Tia (Advances in Business & Industrial Marketing Research, 2024)
The purpose of this study is to examine the intricate interplay between digital disruption and e-business, with a focus on the transformative impact of emerging technologies on competitive dynamics and market structures. The research design and methodology involve a comprehensive review of the literature, drawing insights from academic articles, reports, and scholarly publications to analyze the implications of digital disruption for e-business strategies and practices. The findings and discussion underscore the strategic significance of adopting a customer-centric approach and embracing technological innovation to drive sustainable competitive advantage in the digital era. Key insights include the paramount importance of prioritizing customer experience (CX) optimization initiatives, leveraging emerging technologies such as artificial intelligence (AI) and blockchain, and fostering organizational agility to navigate market disruptions and capitalize on emerging opportunities. The implications of this study extend to both academic and practical contexts, offering valuable insights for academics and practitioners alike. By prioritizing CX optimization, investing in emerging technologies, and cultivating a culture of innovation, e-businesses can position themselves for sustainable growth and competitiveness in the dynamic digital landscape.